Activation of purified soluble guanylate cyclase by protoporphyrin IX. - Ignarro, L J (1982)
Soluble guanylate cyclase [GTP pyrophosphate-lyase (cyclizing), EC 4.6.1.2] purified from bovine lung is markedly activated (30- to 40-fold) by protoporphyrin IX (Ka, 15-25 nM) and is inhibited by hematin (Ki, 3.7 microM) when MgGTP is used as substrate. Guanylate cyclase possesses specific activities (mumol of cGMP per min/mg of protein) of 0.1-0.2 (MgGTP) and 0.3-0.5 (MnGTP) and can attain values of 2-8 (MgGTP) or 1-1.4 (MnGTP) in the presence of protoporphyrin IX. Guanylate cyclase purified in this study contains heme and is activated by nitric oxide and nitrosyl-heme to the same magnitude as that by protoporphyrin IX. With the exception of hematoporphyrin IX, close structural analogs of protoporphyrin IX, including precursors and metabolites, do not activate guanylate cyclase. The insertion of iron into protoporphyrin IX to form heme or hematin renders the metalloporphyrin an inhibitor of unactivated or activated guanylate cyclase. The data suggest that protoporphyrin IX and heme could function to modulate guanylate cyclase activity.